Country Forest Note : Zambia - World Bank (World Bank, Washington, DC, 2020)
This country forest note (CFN) aims to foster dialogue between the World Bank, the government of the Republic of Zambia (GRZ), and key development partners on future engagements in the forestry sector in Zambia by offering a comprehensive analysis of Zambia’s forest sector while shedding light on potential long-term engagements. In response to the government of the Republic of Zambia’s policy and development ambitions to improve the forest sector’s contribution to the national economy, a number of interventions are highlighted in this CFN that could lead to transformative impacts. Data and information available for the forest sector in Zambia is fragmented and inconsistent. This is, in part, due to the lack of consistent monitoring in the context of widespread informality within the forest sector. This CFN partially draws upon secondary data and previous analytical work undertaken by various development partners, combined with official government data. While significant efforts were made to analyze the available data, information gaps are significant. Therefore, the information provided should be carefully interpreted in the context of data limitations.